2023
DOI: 10.1002/adsc.202201297
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic Addition of Nitromethane to Trifluoromethyl Aryl Ketimines Promoted by Electron‐Rich Bifunctional Iminophosphoranes

Abstract: Thiourea-based iminophosphorane (BIMP) organocatalysts featuring SPhos-or BI-DIME phosphine units have been developed and successfully applied in the asymmetric addition of nitromethane to N-Boc-protected trifluoromethyl aryl ketimines. α-Trifluoromethyl β-nitroamines were obtained in 40-82% isolated yields and 80-95% enantioselectivities. A careful evaluation of the catalytic activity of BIMPs indicates that the catalysts derived from the combination via Staudinger reaction of a chiral 1,2-amino alcoholderive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…No product was detected without a base (Table 1, entry 23). The absolute stereochemistry of 3a was determined to be S by comparing its optical rotation with the reported value (Krstic et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No product was detected without a base (Table 1, entry 23). The absolute stereochemistry of 3a was determined to be S by comparing its optical rotation with the reported value (Krstic et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Wang (Xie et al, 2011), Liu (Zhang et al, 2011;Li et al, 2019), and Nenajdenko (Kutovaya et al, 2015) have reported several notable contributions to this field. In addition, Duan (Wang et al, 2019a) and Krstic et al (2023) reported Frontiers in Chemistry frontiersin.org the asymmetric aza-Henry reaction of trifluoromethyl ketimines using different kinds of ion-pair catalysts (Schemes 1A, and B). Despite these advances, the synthesis of chiral trifluoromethyl amines using readily prepared catalysts with low catalyst loading still remains a challenging goal for organic chemists (Onyeagusi and Malcolmson, 2020).…”
mentioning
confidence: 99%
“…In our own work (Scheme 1, D1), phenol nucleophiles were used in the desymmetrization step under ureidopeptide [148][149][150][151][152][153][154] bifunctional iminophosphorane (BIMP) catalysis, [155][156][157][158][159][160][161][162][163][164][165][166][167][168] however, to obtain high levels of enantioselectivity, phenol nucleophiles bearing an ortho-substituent were required, inherently limiting the scope of the reaction. Additionally, the optimal leaving group, 2-nitro-6-methyl-phenolate, 169 is a relatively weak Brønsted base, rendering the turnover of the optimal superbasic BIMP catalyst inefficient, which, in turn, forces an excessive 15 mol% catalyst loading to ensure high conversion of the starting material to product.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the bifunctional iminophosphorane−thioureabased iminophosphorane (BIMP) organocatalyst featuring a BIDIME iminophosphorane unit and thiourea motif was able to mediate the enantioselective addition of nitromethane to trifluoromethyl aryl ketimines to furnish α-trifluoromethyl-βnitroamines in good yields and enantioselectivities (Scheme 60). 116…”
Section: Asymmetric Addition To C−n Double Bondsmentioning
confidence: 99%
“…Scheme 60. Enantioselective Organocatalytic Addition of Nitromethane to Trifluoromethyl Aryl Ketimines116 …”
mentioning
confidence: 99%